Study on Separation, Purification, Structural Characteristics and in Vitro Antioxidant Activity of Polysaccharides from Chinese Yam Peel - Meizhi YE; Ziyi WU; Jinsong WU; Qingping ZHONG (Shipin gongye ke-ji, 2023)
In this study, the optimal process for the deproteinization of crude polysaccharides from Chinese yam peel was investigated by using the trichloroacetic acid method, Sevag method and Sevag-papain enzyme method. The purified polysaccharide fractions were characterized by infrared spectroscopy, the monosaccharide composition analysis, and the antioxidant activity in vitro was determined. The results indicated that the optimal ethanol final concentration was 90%, the yield of polysaccharide reached 9.55%, and polysaccharide precipitation rate was the highest. The better deproteinization process was papain treatment combined with Sevag method. Under the condition, the polysaccharide retention rate reached 64.7% and the deproteinization rate was 76.8%. Two major polysaccharide fractions named CYPP-1 and CYPP-2 were isolated and purified from crude polysaccharide by DEAE-52 cellulose column chromatography, and their molecular weights were 4.442 kDa and 4.278 kDa respectively. CYPP-1 was consisted of glucosamine hydrochloride, galactose, glucose, mannose and glucuronic acid with the molar ratio of 11.1:14.4:21.8:35:10.8, and CYPP-2 was consisted of glucosamine hydrochloride, mannose and glucuronic acid with the molar ratio of 10.5:47.9:16.8. Infrared spectroscopy showed that both fractions were consistent with the structural characteristics of plant polysaccharides, being α-type polysaccharides. The scavenging effects of different concentrations of CYPP-1 and CYPP-2 on DPPH, hydroxyl radicals, ABTS+ and superoxide anion radicals in vitro were compared, and the scavenging rates of 8.0 mg/mL CYPP-1 were 89.83%, 46.72%, 67.27% and 51.20%, respectively. And its antioxidant activity was higher than that of CYPP-2.